2020
DOI: 10.3390/fi12030055
|View full text |Cite
|
Sign up to set email alerts
|

Security of IoT Application Layer Protocols: Challenges and Findings

Abstract: IoT technologies are becoming pervasive in public and private sectors and represent presently an integral part of our daily life. The advantages offered by these technologies are frequently coupled with serious security issues that are often not properly overseen or even ignored. The IoT threat landscape is extremely wide and complex and involves a wide variety of hardware and software technologies. In this framework, the security of application layer protocols is of paramount importance since these protocols … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(48 citation statements)
references
References 68 publications
0
46
0
2
Order By: Relevance
“…Finally, Application layer security involves the security vulnerabilities and prevention mechanism detected and, respectively, implemented at communication protocol layer. It is worth mentioning IoT protocol solutions such as MQTT, CoAP and less-typical IoT protocols AMQP, DDS, and XMPP [ 40 ]. MQTT is widely used in IoT platforms.…”
Section: Security In the Internet Of Thingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, Application layer security involves the security vulnerabilities and prevention mechanism detected and, respectively, implemented at communication protocol layer. It is worth mentioning IoT protocol solutions such as MQTT, CoAP and less-typical IoT protocols AMQP, DDS, and XMPP [ 40 ]. MQTT is widely used in IoT platforms.…”
Section: Security In the Internet Of Thingsmentioning
confidence: 99%
“…Moreover, message validation mechanisms that are improperly implemented (for example, a publisher sends messages consisting of invalid characters that cannot be correctly interpreted by brokers and subscribers), facilitate security attacks. Man-in-the-middle (MiTM) attacks [ 40 ] may happen as the encryption is performed only for payloads, not for the entire message [ 41 ].…”
Section: Security In the Internet Of Thingsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is capable to ensure the integrity of the software and configuration of all the nodes and, thus, to avoid the exchange of incorrect synchronization information over secure protocols. For a more complete view on prior works about SW vulnerabilities in other domains, interested readers can also refer to [29][30][31] and the references therein.…”
Section: Master Clockmentioning
confidence: 99%
“…The AMQP standard consists mainly of [51]: message, the key element of the entire communication process; producer, creates a message and sends it; broker, distributes the message according to rules defined to different queues; and finally, consumer, which takes the message from the queue where it can access and reprocess it. The security aspects and threats were analyzed in [52]. In particular, the authors showed that AMQP could be exploited by using common threats such as replay [53], masquerade, modification, and denial of service [54].…”
Section: Related Workmentioning
confidence: 99%